2013
DOI: 10.1371/journal.pone.0061111
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field-Driven Water Dipoles: Nanoscale Architecture of Electroporation

Abstract: Electroporation is the formation of permeabilizing structures in the cell membrane under the influence of an externally imposed electric field. The resulting increased permeability of the membrane enables a wide range of biological applications, including the delivery of normally excluded substances into cells. While electroporation is used extensively in biology, biotechnology, and medicine, its molecular mechanism is not well understood. This lack of knowledge limits the ability to control and fine-tune the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…First, we are working at frequencies or on time scales where the relative dielectric permittivity of water is much less than 80 (Barthel et al 1990). Second, the intrusion of individual water molecules from the complex dielectric landscape of the membrane interface to the low-permittivity environment of the lipid bilayer interior is a phenomenon much better treated in atomic detail, where macroscale material properties like permittivity are of limited utility (Tokman et al 2013). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we are working at frequencies or on time scales where the relative dielectric permittivity of water is much less than 80 (Barthel et al 1990). Second, the intrusion of individual water molecules from the complex dielectric landscape of the membrane interface to the low-permittivity environment of the lipid bilayer interior is a phenomenon much better treated in atomic detail, where macroscale material properties like permittivity are of limited utility (Tokman et al 2013). …”
Section: Resultsmentioning
confidence: 99%
“…What happens in the simulations is contrary to these expectations. The stabilization of intruding interfacial water by the applied electric field (Tokman et al 2013) is not reversed when the field direction changes. The water bridges grow, rather than shrink, cycle after cycle, drawing the phospholipid head groups after them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer simulations using recent advances in molecular dynamics approaches to describe membrane behavior under the influence of an applied electric field have suggested that once the membrane reaches the critical point, water molecules begin to gain access across the membrane and an inverted hydrophilic pore can be formed (Figure 2) (Delemotte & Tarek, 2012; Ho, Casciola, Levine, & Vernier, 2013; Ho, Levine, & Vernier, 2013; Kramar et al, 2012; Polak et al, 2013; Tokman et al, 2013). With continued application in the field, this metastable hydrophilic pore can transition to a larger, more stable pore that can allow the transport of larger charged macromolecules.…”
Section: Theory Of Membrane Electroporationmentioning
confidence: 99%
“…Based on an energetic analysis, Tokman and co-authors recently suggested that pore formation in response to an intense electric field is driven by the reorganization of water molecules in columnar stacks at the membrane interface [14]. They showed that an electric field of sufficient intensity stabilizes columnar water dipole arrays oriented along the applied field while it destabilizes planar water configuration perpendicular to the field direction.…”
Section: Introductionmentioning
confidence: 99%